Impacts of gamifying English learning in higher education on EFL learners’ achievement and aptitude: A mixed-methods study - Ayiz, Abdul; Priyatmojo, Arif Suryo; Atmantika, Zanuwar Hakim; Tauchid, Ahmad; Karima, Nahla Hilyatul (EduLite: Journal of English Education, Literature and Culture, 2026)
English proficiency and learner aptitude remain central outcomes in higher education, yet motivating sustained engagement among EFL students is an ongoing pedagogical challenge. This mixed-methods quasi-experimental study examined whether gamified English instruction enhances undergraduate EFL students’ achievement and aptitude. Eighty-three intermediate-level students (N = 83; 41 experimental, 42 control; 35 female, 48 male) participated in a six-week (12-session) intervention in which the experimental group experienced a gamified learning environment (points, levels, badges, leaderboards) integrated with course content, while the control group received equivalent conventional instruction. The quantitative measures comprised a 42-item achievement test (vocabulary, grammar, reading, writing) and an adapted 15-item aptitude questionnaire (motivation, enjoyment, self-efficacy, gendered preferences, technology/usability) and were analysed using descriptive statistics and paired-sample t-tests, while the qualitative data were collected via weekly reflections and focus-group interviews and were analysed thematically. Results indicate a statistically significant improvement in achievement for the gamified cohort: pretest M = 67.85 (SD = 7.63) to posttest M = 81.49 (SD = 6.72), t(82) = −10.42, p < .001, Cohen’s d = 1.32. Aptitude scores were strongly positive overall (M = 4.32, SD = 0.53), with enjoyment and motivation scoring highest. Gender analyses revealed negligible differences in gains between males and females. Thematic analysis highlighted increased motivation and reduced anxiety, enhanced peer collaboration, and greater learner autonomy and self-monitoring. Findings suggest that well-designed gamification can simultaneously foster affective engagement and measurable language gains in tertiary EFL contexts; implications include adopting gamified elements to support blended curricula and further research on sustainability and cultural moderation.